2003
DOI: 10.1023/a:1024360204239
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: ABSTRACT. This paper examines the views of proof held by university level mathematics students and teachers. A framework is developed for characterizing people's views of proof, based on a distinction between public and private aspects of proof and the key ideas which link these two domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…Mathematical thinking is revealed through the ability of a person to argue his actions and ideas. Raman (2003) explores the nature of the proof, various approaches to argumentation in the course of mathematical activity. The author shows the difference between mathematical proof and other sciences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mathematical thinking is revealed through the ability of a person to argue his actions and ideas. Raman (2003) explores the nature of the proof, various approaches to argumentation in the course of mathematical activity. The author shows the difference between mathematical proof and other sciences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Beyond the function of proof, several researchers speak about different types of proofs, putting the focus on this global understanding or empowerment that is deeply connected to proof, and Smith [19] makes a good synthesis of some of these distinctions. That is the case with Hanna [32], who distinguishes between 'proofs that explain' and 'proofs that prove'; the case with Tall [33], who speaks about 'logical' and 'meaningful' proofs; the case with Weber & Alcock [34], who distinguish between 'syntactic' and 'semantic' proofs; and the case with Raman's [35], who focuses on the kind of ideas used in the proof and considers 'heuristic ideas' and 'procedural ideas,' with the concept of a 'key idea' linking the two. The points of view of these authors are slightly different, but as Smith [19, p. 75] emphasizes, what all of them seem to be addressing is two distinct approaches to mathematical proof: 'a procedural, logical approach on which the prover's intuition is not necessarily engaged, and an approach relying on the prover's intuitive understanding of the mathematical structure involved'.…”
Section: Functions Of Proof: From Mathematics To School Mathematicsmentioning
confidence: 99%
“…Existence of numerous national and international studies on individuals' weaknesses or misconceptions about theorem and proof (Almeida, 2000;Arslan and Yıldız, 2010;Arslan,2007;Aydoğdu, Olkun and Toluk, 2003;Bahtiyari, 2010;Coşkun, 2009;Dane, 2008;Dreyfus, 1999;Güven, Çelik and Karataş, 2005;Harel and Sowder, 1998;İmamoğlu, 2010;Jones, 2000;Moore, 1990Moore, , 1994Moralı, Uğurel, Türnüklü, and Yeşildere, 2006;Özer and Arıkan, 2002;Raman, 2002Raman, , 2003Recio and Godino, 2001;Sarı, Altun, and Aşkar, 2007;Selden and Selden, 2003;Shipley, 1999;Stylianides, Stylianides and Philippou, 2007;VanSpronsen, 2008;Weber, 2001Weber, , 2005 shows that the gaps or misconceptions related to theorem and proof are not peculiar only to Turkish context. Studies, among these subjects, have focused on proof which is regarded very important for developing mathematical thinking (Hanna, 2000;Moralı, Köroğlu and Çelik, 2004;Moralı et al, 2006) and can be used as a means of persuading people (Harel, 2008;Harel andSowder, 1998, 2007) (persuading people would decrease the undesirable social events).…”
mentioning
confidence: 99%
“…Beside these, in NCTM in 2000, it is reported that proof is an effective way which can be used in developing and explaining instincts. Studies with the purpose to find out the reasons underlying the difficulties with proof which is an important phenomenon show that students cannot remember what proof is (Moore, 1994;Raman, 2003), do not have right ideas about what a mathematical proof consists of (Weber, 2001), and cannot understand the concept of proof (Dane, 2008;Güler and Dikici, 2012;Moore, 1994). Defining a subject matter difficult or easy vary according to various criteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation